Floriculture Center an integrated research, service and exhibition facility for ornamental horticulture - Abrajano, Maria Angelica E. (College of Architecture, University of the Philippines Diliman, 2014)
The study focuses on a research and service center with a specific need for collaboration and integration. The Floriculture Center is meant to be core facility that could open the gates for research on new knowledge that can be applied to the ornamental horticulture industry of the Philippines. This development could come up with innovative ways for additional floriculture technology for a wider reach to export countries. It is expected to meet the need for centralization and organization in the industry. What is the status of the flower industry in the Philippines? How are the spaces in a floriculture facility linked to the processes of research, trade and learning among other aspects of human use? What design approach of a floriculture center could be appropriate to the culture and context of cut flower industry in the country? These questions will serve as a basis to create a highly-competitive and revitalized facility that is adaptable by series of events- a facility that provides spaces and extension services needed to uplift the current situation of the Philippine ornamental horticulture and at the same time ignites the awareness of Filipinos towards the benefits that can be derived from the industry.